The Effect Of Five-Factor Model Ofpersonality And Religiosity Toward Adolescents’s Resilience Whoose Parents Are Divorced - Dimas Reza Narendra; Natris Indriyani (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
The objective of this study is to examine the effect of five-factor model of personality (agreeableness, conscientiousness, emotional stability, intellect, surgency) and religiosity (forgiveness, general religiosity, god as judge, involved god, social religiosity, thankfulness, unvengefulness) toward adolescents’s resilience whoose parents are divorced in Indonesian. Samples are 158 adolescents whoose 15-22 years old and had a parental-divorced experience. Sampling technique is convenience sampling. The scales are modified from Resilience Quotient, Mini-IPIP, and Religiosity Scale from Kendler. The validity of the scales are examined by confirmatory factor analysis (CFA). The data is analized by multiple regression analysis technique. The result of this study shows that five-factor model of personality and religiosity have significant effect toward the resilience among adolescents. The minor hypothesis examination shows that only intellect model of personality and general religiosity which have significant effect toward dependent variable. We hope that the implication of this study could be re-examined an developed in the next study. Therefore, for the next study, we suggest to use bigger sample size and participate other independent variables such as self-esteem, hopelessness, stress-coping, loneliness, hope, social support, optimism, demografic fartors, etc. Penelitian ini bertujuan untuk mengetahui pengaruh model kepribadian lima faktor (agreeableness, conscientiousness, emotional stability, intellect, surgency) dan religiusitas (forgiveness, general religiosity, god as judge, involved god, social religiosity, thankfulness, unvengefulness) terhadap resiliensi remaja korban perceraian di Indonesia. Sampel penelitian berjumlah 158 remaja berusia 15-22 tahun yang memiliki pengalaman atas perceraian kedua orangtuanya. Teknik pengambilan sampel yang digunakan adalah convenience sampling. Peneliti memodifikasi alat ukur Resilience Quotient, Mini-IPIP, dan Religiusitas Kendler. Uji validitas alat ukur menggunakan teknik Confirmatory Factor Analysis (CFA). Analisis data menggunakan teknik analisis regresi berganda. Hasil penelitian menunjukkan bahwa ada pengaruh yang signifikan dari model kepribadian lima faktor dan religiusitas terhadap resiliensi subjek penelitian. Hasil uji hipotesis minor yang menguji pengaruh masing-masing variabel bebas terhadap variabel terikat menunjukkan bahwa hanya model kepribadian intellect dan general religiosity yang memberikan pengaruh terhadap resiliensi subjek penelitian secara signifikan. Peneliti berharap implikasi dari penelitian ini dapat dikaji kembali dan dikembangkan pada penelitian selanjutnya. Adapun untuk penelitian selanjutnya, disarankan agar menggunakan jumlah sampel yang lebih besar dan melibatkan berbagai variabel bebas lainnya yang juga berkaitan dengan resiliensi seperti self-esteem, hopelessness, coping stress, loneliness, harapan, dukungan sosial, optimisme, faktor demografi, dan lain sebagainya. DOI: 10.15408/jp3i.v6i1.8149